Inductive Programming Meets the Real World. - GULWANI, SUMIT; HERNÁNDEZ-ORALLO, JOSÉ; KITZELMANN, EMANUEL; MUGGLETON, STEPHEN H.; SCHMID, UTE; ZORN, BENJAMIN (Communications of the ACM, 2015)
The article looks at how the integration of inductive programming (IP) techniques in software applications can support end users in automating complex tasks. Details are provided on the process of learning domain-specific programs from observations on how users interact with the system. Noted applications of IP include spreadsheet tools, scripting, and intelligent program tutors.